Pengaruh Profitabilitas, Tax Planning dan Keputusan Investasi Terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Pemoderasi di Asia Tenggara - Sihar Tambun; Riska Dewi Setyowati; Riris Rotua Sitorus (Media Akuntansi Perpajakan, 2026)
This research aims to prove or focus on how profitability, tax planning and investment decisions influence company value by moderating good corporate governance in Southeast Asia). Apart from that, to prove the moderating impact of good corporate governance if it is collaborated with the variables in the title of this research, whether it can strengthen or weaken the influence variables of profitability, tax planning and investment decisions on the firm value variable . The population of this research is all food and beverage companies listed on the stock exchanges of Southeast Asian countries. Samples were taken from five countries, namely Indonesia, Malaysia, Singapore, Thailand and the Philippines. The research period is 3 years, namely 2022 to 2024. The number of samples taken from each country is 10 companies. The sample determination method uses purposive sampling with three criteria. First, the issuer is included in the 10 companies with the largest turnover. Second, it was listed on each country's stock exchange during the research period and was never delisted. Third, publish financial reports and annual reports on the stock exchange website or on the respective company websites and can be accessed by researchers. The research method used is a quantitative method and tested using moderated regression analysis. Moderation regression analysis consists of direct effect and moderating effect tests. The moderating effect is carried out using the interaction method, namely the interaction between the good corporate governance variable and the variables influencing profitability, tax planning and investment decisions.